Peculiarities of the classification of raw-smoked sausages during forensic commodity examination (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The main identification tasks of commodity examination of raw-smoked sausages are establishing their authenticity, determining compliance with safety and quality standards. To achieve these tasks, forensic experts conduct a number of studies and determinations, which include determining the composition of the product, determining the composition, quality and quantity of components, determining compliance with quality standards, as well as determining the content of atypical impurities and impurities. Carrying out these identification tasks, the examination allows to ensure the quality and safety of the product and forms the protection of consumer rights. Defects in raw-smoked sausages can occur for a variety of reasons and are usually the result of deficiencies in production, storage, or transportation.The scientific article outlines the methodological features of conducting a forensic commodity examination of raw-smoked sausages, analyzes the theoretical and practical problems of the commodity research of raw-smoked sausages, defines the commodity aspects of raw-smoked sausages and their defects, systematizes information data on the algorithm for conducting a forensic commodity examination of raw-smoked sausages in order to check for the presence of characteristic defects. The stages of conducting a forensic commodity examination of raw smoked sausages are listed. Recommendations for quality assessment of raw-smoked sausages for expert organizations and consumers are offered. Prospective instrumental methods of examination of raw smoked sausages are defined, in particular spectral analysis, chromatographic methods, mass spectrometry, microscopy, thermal analysis; the main microbiological procedures that can be used during the examination of raw-smoked sausages are described; characteristic defects of raw-smoked sausages are summarized, including those that indicate its low quality or may be a sign of spoilage; describes the general sequence of actions that occur during the examination of this product.